2016
DOI: 10.2147/copd.s97343
|View full text |Cite
|
Sign up to set email alerts
|

COPD assessment test and severity of airflow limitation in patients with asthma, COPD, and asthma–COPD overlap syndrome

Abstract: ObjectiveThe COPD assessment test (CAT) consists of eight nonspecific scores of quality of life. The aim of this study was to compare the health-related quality of life and severity of airflow limitation in patients with asthma, COPD, and asthma–COPD overlap syndrome (ACOS) using the CAT.MethodsWe examined CAT and lung functions in 138 patients with asthma, 99 patients with COPD, 51 patients with ACOS, and 44 patients with chronic cough as a control. The CAT score was recorded in all subjects, and the asthma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
6
23
0
Order By: Relevance
“…ACO was considered as one of the phenotypes of COPD. Our study showed that ACO was independently associated with the total CCQ and symptom and functional domain scores, which was consistent with findings of other studies, in which subjects with ACO suffered from higher symptom burden than those with COPD alone [41][42][43].…”
Section: Discussionsupporting
confidence: 93%
“…ACO was considered as one of the phenotypes of COPD. Our study showed that ACO was independently associated with the total CCQ and symptom and functional domain scores, which was consistent with findings of other studies, in which subjects with ACO suffered from higher symptom burden than those with COPD alone [41][42][43].…”
Section: Discussionsupporting
confidence: 93%
“…However, asthma control was assessed according to the GINA 2010 report [29]; thus, impaired lung function might partially explain the poor control of asthma in the present study. Previously, it has been suggested that ACOS patients might have higher CAT scores than patients with asthma [39]. Therefore, we evaluated whether ACOS can be distinguished from asthma, using questionnaires that have been validated for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that the CAT score is also a useful tool in asthma [34][35][36], while asthma control test (ACT) is disease-specific and focuses on asthma control only.…”
Section: Limitationsmentioning
confidence: 99%